Human IgG antibody response to Aedes aegypti Nterm‐34 kDa salivary peptide as an indicator to identify areas at high risk for dengue transmission: a retrospective study in urban settings of Vientiane city, Lao PDR. Issue 5 (20th February 2014) - Ndille, Emmanuel Elanga; Dubot‐Pérès, Audrey; Doucoure, Souleymane; Mouchet, François; Cornelie, Sylvie; Sidavong, Bounpone; Fournet, Florence; Remoue, Franck
Abstract Objective Using human IgG antibody response to the Aedes Nterm‐34 kDa salivary peptide as an indicator of human exposure to Aedes bites in surveying exposed populations from areas at risk of dengue virus (DENV) transmission in urban settings of Vientiane city, Lao PDR. Methods Enzyme‐linked immunosorbent assay tests were performed to measure the IgG response to Nterm‐34 kDa peptide in blood samples collected within a flavivirus seroprevalence survey carried out in 2006 including 3558 randomly selected individuals. The level of IgG response to the Nterm‐34 kDa peptide in individuals was analysed in relation to the level of urbanisation of the individual's residence, areas that presented significant differences in the prevalence of recent DENV infection. Results No differences were observed in the anti‐Nterm‐34 kDa IgG level between DENV‐positive and DENV‐negative individuals. However, the level of specific IgG response was higher among individuals living in slightly urbanised neighbourhoods than among those in more highly urbanised areas (P < 0.0001). Interestingly, a similar pattern had already been observed concerning the prevalence of recent DENV infection in the same populations. Conclusion The results of this retrospective study indicate that the evaluation of human IgG response to the Aedes Nterm‐34 kDa salivary peptide could be a useful indicator to identify places with risk of dengue virus transmission in urban endemic areas.